Comment on "Point defect structure of La-doped SrTiO3 ceramics with colossal permittivity". (1st January 2021) - Tkach, Alexander; Okhay, Olena
Abstract: With this contribution, as a comment to the publication in Acta Materialia 164 (2019) 76, reporting point defect structure and giant dielectric response in La-doped strontium titanate ceramics, we show that the reported ceramics should have a strong effect of O vacancies instead of possessing displaced Ti, Ti vacancies and Schottky defects within their crystal lattice and therefore suggested mechanisms for the giant permittivity response have to be reconsidered. Some data analysis are also found to be contradictive to the literature or incomplete.